Inovasi dalam Praktik Akad Mudharabah: Tinjauan Terhadap Pengembangan Produk Keuangan Islam - Abdul Chadjib Halik; Nasrullah Bin Sapa; Rahman Ambo Masse (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The Islamic finance industry has grown significantly, emphasizing the need for a profound understanding of Mudharabah practices to foster innovation and competitiveness. This qualitative study explores the understanding, barriers, and innovation potential of Mudharabah within Indonesia's Islamic banking sector. Using a descriptive research design, ten respondents from various positions in Islamic banks were interviewed via purposive sampling. Data were collected through semi-structured interviews and document analysis. Most respondents strongly grasped Mudharabah's fundamental concepts but encountered challenges in technical implementation and regulatory comprehension. Major barriers included regulatory complexity, public awareness, Shariah risk management, and operational infrastructure limitations. Potential innovations identified include blockchain technology, digital risk management, technology-driven products, and data-centric approaches. Implementing these innovations could enhance Islamic financial institutions' efficiency, transparency, and competitiveness. The study underscores the importance of intensive training, regulatory reforms, and collaborative efforts among institutions to support the Islamic finance industry's growth. This research aims to advance understanding of Mudharabah practices and catalyze the development of innovative, market-relevant Islamic financial products.